Current state of Fusarium wilt of banana in the subtropics - Dita Rodriguez, Miguel Angel; Teixeira, L; O’Neill, Wayne; Pattison, Tony; Weinert, Mathew; Li, Chunyun; Zheng, Sijun; Staver, Charles; Thangavelu, Rhaman; Viljoen, Altus (International Society for Horticultural Science, 2020)
The original publication is available at https://www.actahort.org/books/1272/1272_7.htm